2016
DOI: 10.3390/su8080772
|View full text |Cite
|
Sign up to set email alerts
|

Forested Land Use Efficiency in China: Spatiotemporal Patterns and Influencing Factors from 1999 to 2010

Abstract: Abstract:More attention needs to be paid to efficiency in the use of forested land. This article is devoted to the study of forested land use efficiency (FLUE) and its spatiotemporal differences in China during the period from 1999 to 2010. The global generalized directional distance function (GGDDF) and global Malmquist-Luenberger (GML) index models are used to measure and analyze forested land use efficiency. The empirical results showed that forested land use efficiency continued to increase during the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…For the central region, the progress in forested land productivity derived mostly from improvements in efficiency. The change in the productivity of forested land in the western region resulted from the interactive effect of these two decompositions [6]. These findings imply that environmentally friendly green growth policies should be managed differently depending on the unique conditions of regional economic activities and their environmental settings.…”
Section: Governance Issues For the Sustainability Of Asiamentioning
confidence: 98%
See 2 more Smart Citations
“…For the central region, the progress in forested land productivity derived mostly from improvements in efficiency. The change in the productivity of forested land in the western region resulted from the interactive effect of these two decompositions [6]. These findings imply that environmentally friendly green growth policies should be managed differently depending on the unique conditions of regional economic activities and their environmental settings.…”
Section: Governance Issues For the Sustainability Of Asiamentioning
confidence: 98%
“…Since this difference comes from a very complicated mixture of urbanization, economic development contexts, and population density (as shown in the model), it is not easy and effective for the central government to mitigate these differences. To mitigate this gap, Yafen He et al tried to examine the dynamic changes in the FLUE, and found that the productivity of forested land was always increasing, and that changes in the productivity of forested land in the eastern region derived mostly from technological advances [6]. For the central region, the progress in forested land productivity derived mostly from improvements in efficiency.…”
Section: Governance Issues For the Sustainability Of Asiamentioning
confidence: 99%
See 1 more Smart Citation
“…According to the data provided by the IPCC (2006), the world's productive lands (forests, grasslands, arable lands, gardens, and other agricultural lands) contain a large amount of carbon stock. The carbon storage of forests and grasslands accounts for 93% of the total carbon stock of productive lands [42][43][44]. In fact, the climate impacts are global and do not pertain only to the specific area where passengers generate the carbon emissions.…”
Section: Carbon Footprint Model For Passenger Transportmentioning
confidence: 99%
“…The study found that the increase in TFP in the western region was mainly due to technological progress. The increase in TFP in the central region was mainly due to Sustainability 2018, 10,1932 4 of 32 the scale expanding [26]. Xie used the GML index to measure the TFP of cultivated land green use in China from 1995 to 2013 under the constraint of agricultural nonpoint source pollution and noted that improving production techniques and improving the ecological environment will help improve the TFP of cultivated land green use [27].…”
Section: Literature Reviewmentioning
confidence: 99%